Capacity Building of Village-Owned Enterprises (BUMDes) in Encouraging Village Economic Welfare - Adeningsih, Siti Hutami (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to examine the capacity building of village-owned enterprises (BUMDes) in encouraging village economic welfare based on the organizational capacity theory from Grindle (1997) which has three main indicators, namely strengthening organization and management, providing resources and infrastructure facilities, and network. The research method in this study is qualitative descriptive with the technique of collecting literature study data from various secondary sources such as books, scientific articles, government regulations, theses and other relevant scientific documents. Data analysis is carried out by data reduction, data presentation to drawing conclusions. The results of the study show that based on the Grindle theory (1997), strengthening the capacity of BUMDes can be done by measuring from three indicators, namely 1) strengthening organization and management; 2) provision of resources and infrastructure; 3) Network (cooperation). ). The success of strengthening BUMDes capacity based on Grindle's theory greatly influences the sustainability and operation of BUMDes.